Prototipo de Riego Inteligente para la Optimización de Recursos Hídricos en Parques y Jardines con Tecnología Open Source - Torres Salinas, Juan Carlos (2020)
The present project is focused on developing an intelligent water supply control and irrigation optimization system in residential green areas, which is why in order to support the functionality of the prototype, installation has been carried out in a residential garden in the canton Catamayo province from Loja. This prototype is an automated design that is mostly made up of OPEN SOURCE technology in both hardware and software, with transducers that will allow the state of soil moisture to be censored and, in addition, is based on a database that stores information on weather forecasts, obtained by accessing the internet itself that will allow the system to develop a sophisticated control environment and thus be able to take advantage of rainwater, and save water mainly in areas of low rainfall, on the other hand There is a graphic interphase that will allow the System to interact with the User.